Zastosowanie strategii zabezpieczającej przed ryzykiem zmiany kursu walutowego w kontraktach futures na Warszawskiej Giełdzie Towarowej - Krawczyk, Ewa (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2007)
On the Warsaw Commodity Exchange there are quoted futures on agricultural goods and financial instruments. Futures can be used to hedge against unfavourable changes on the cash market. In the paper the model of hedging use in futures on euro was presented. Two scenarios of hedging use were worked out: pessimistic and optimistic. The analysis showed, that thanks to sale hedging, within both of the scenarios, a negative impact of foreign exchange risk on the financial result of wheat sale on the cash market was minimised. An investor was secured of profit from the transaction at the level of 260,000 zloty